Injuries in combined events: epidemiological data from national-level championships - Edouard, P.; Morin, J.-B.; Samozino, P. (New Studies in Athletics, 2013)
ABSTRACT Several studies have reported that competitors in the combined events are at greater risk of injury than those in other disciplines at major international athletics events. The aim of this study was to expand current knowledge by examining the incidence and characteristics of injuries incurred in a national-level competition. At the 2010 French National Combined Events Championships, all newly occurring injuries were prospectively recorded using a methodology developed for the International Olympic Committee. Fifty-one injuries including nine time-loss injuries, were reported among 107 athletes (477 injuries and 84 time-loss injuries per 1000 athletes), a rate even higher than at elite international competitions. Interestingly, the higher risk largely concerned the younger athletes and is thus a concern because of possible impacts on their vulnerable, immature musculoskeletal structures. It was also found that approximately 72% of the injuries affected the lower limbs, thigh strain (17.6%) being the most common diagnosis, and 60% of the injuries were caused by overuse. Based on this finding, the authors conclude by recommending that preventive interventions should mainly focus on overuse and thigh injuries. This article is adapted from a paper published in the International Journal of Sport Medicine.